Managing Oromandibular Hardware Failure after Free Flap Surgery - Domack, Aaron M.; Silverman, Dustin A.; Tang, Alice L.; Zender, Chad A.; Patil, Yash J. (Seminars in Plastic Surgery, 2022)
Hardware failure after oromandibular reconstruction using free tissue transfer can delay additional therapies directed at cancer treatment and prevent patients from returning to normal oral function. Understanding and strict adherence to principles of rigid fixation is critical in preventing complications. Early surgical intervention for hardware exposure as well as utilization of locoregional flaps may prevent the need for more extensive revision surgery.
Keywords: hardware failure; free flap; free tissue transfer; surgical complications